Advance directives or living wills- some reflections from general practitioners and frail care coordinators in a small town in KwaZulu Natal - Bull, A. P. A. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2012.